Analysis of Students’ Analytical Thinking Skills in Biology Learning through the Problem-Solving Model Based on Socio-Scientific Issues - Safitri, Rya Angraini; Alberida, Heffi; Fadilah, Muhyiatul; Fajrina, Suci (Universitas Sultan Ageng Tirtayasa, 2023)
This research aimed to analyze analytical thinking skills of students in biology learning through a problem-solving model based on socio-scientific issues. The method was experimental that used a One-Group Pretest-Posttest design. The subjects in this research were students of class X in senior high school. The instrument was in the form of pretest-posttest questions that measure three indicators of the ability to think analytically; differentiating, organizing, and attributing. Data analysis was performed using the Mann-Whitney U Test and gain scores for each indicator of analytical thinking ability. The results of the study show the sig. (2-tailed) 0.000 which is less than 0.05. In addition, the experimental class gain value is 0.6 in the quite effective category. Based on the research results, learning biology by implementation of problem-solving models based on socioscientific issues has a positive effect on improving students' analytical thinking skills. As a result, students can come up with new ideas, evaluate the information they find, understand concepts, and solve complex problems.